1999
DOI: 10.1097/00001756-199911080-00004
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis of cerebral clot embolism in rat

Abstract: Rats submitted to focal cerebral ischemia by middle cerebral artery clot embolism were treated with recombinant tissue plasminogen activator (rt-PA) at increasing delays (1.5, 3 and 4.5 h) after the onset of ischemia. Treatment efficacy was evaluated by NMR imaging of the apparent diffusion coefficient of water (ADC). In untreated animals the size of the ADC-detectable lesion gradually increased after clot embolism, expanding over 8 h to 174 +/- 17% of the volume visible at 30 min. Thrombolysis initiated 1.5 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 7 publications
3
26
0
1
Order By: Relevance
“…However, the success of the tissue plasminogen activator (tPA) trial with a 3-hour time window [7] shows that such studies are possible. It is noteworthy that tPA is also effective in animal stroke models within the same time frame [8], supporting the idea that animals and humans may be similar in the time their window of opportunity is open. Most investigated compounds act on the early events in the neurodegenerative cascade.…”
Section: Therapeutic Windowmentioning
confidence: 81%
“…However, the success of the tissue plasminogen activator (tPA) trial with a 3-hour time window [7] shows that such studies are possible. It is noteworthy that tPA is also effective in animal stroke models within the same time frame [8], supporting the idea that animals and humans may be similar in the time their window of opportunity is open. Most investigated compounds act on the early events in the neurodegenerative cascade.…”
Section: Therapeutic Windowmentioning
confidence: 81%
“…6 Furthermore, Brinker and colleagues 8 showed that HTs can reliably be induced in SHR by means of the presently used animal model and timing conditions for treatment. Thus, although rtPA treatment is performed at this time point, no confounding effect by any treatment success would hide the bleeding aspects of our study.…”
Section: Animal Preparationmentioning
confidence: 99%
“…However, basing pretreatment decisions on such signatures may lead both to unjustified inclusions and exclusions of stroke patients: unjustified inclusions because hemorrhages have been observed in undamaged brain 5 and unjustified exclusions because thrombolytic protection of the penumbra may lead to the significant reduction of final lesion size, even if the infarct core is irreversibly damaged and cannot be salvaged. 6,7 This raises the question of whether hemorrhages can be predicted by MRI irrespective of the severity of the ischemic injury.…”
mentioning
confidence: 99%
“…27 The evaluation of the dynamics of the ADC changes confirmed our earlier observation that the reduction of the biochemical lesion volume is not due to the reversal of the initial ischemic injury but to the prevention of infarct growth. 9,28 This explains why the therapeutic efficacy declines with increasing treatment delay. In fact, comparison of ADC recordings after different treatment delays revealed that rtPA freezes the lesion volume at the level it has reached when treatment begins.…”
Section: Rtpa-induced Reduction Of Tissue Injurymentioning
confidence: 99%
“…In fact, comparison of ADC recordings after different treatment delays revealed that rtPA freezes the lesion volume at the level it has reached when treatment begins. 28 Because up to this time ADC volume steadily expands, the salvageable tissue mass declines accordingly.…”
Section: Rtpa-induced Reduction Of Tissue Injurymentioning
confidence: 99%